Thermal management of methanol reforming reactors for the portable production of hydrogen. (24th January 2020) - Chen, Junjie; Li, Linke
Abstract: Three-dimensional numerical simulations were performed to address the thermal management issues associated with the design of a methanol reforming microchannel reactor for the portable production of hydrogen. The design of the reactor was fundamentally related to the direct coupling of reforming and combustion reactions by performing them on opposite sides of dividing walls in a parallel flow configuration. Effective autothermal operation was achieved through a combination of microchannel reactor technology with heat exchange in a direction perpendicular to the reacting fluid flow. Computational fluid dynamics simulations and thermodynamic analysis were carried out to investigate the effect of various design parameters on the characteristics of the generation, consumption, and exchange of thermal energy within the system. The results indicated that the ability to control temperature and temperature uniformity is of great importance to the performance of the system. The degree of temperature uniformity favorably affects the autothermal operation of the reactor. Temperature uniformity of the reactor can be improved by controlling the rate of heat transfer through a variety of factors such as wall thermal conductivity, fluid velocities, and dimensions. High wall thermal conductivity would be greatly beneficial to the performance of the system and the temperature uniformity of the reactor. Graphical abstract: Image 1 Highlights: The degree of thermal uniformity favorably affects reactor autothermal operation. Wall thermal conductivity plays a significant role in reactor thermal uniformity. Relatively high fluid velocities are required to reduce heat exchange resistance. Reactor dimensions should be carefully designed to ensure good thermal management. Thermodynamic analysis is an effective way to identify heat transfer mechanisms.